2014
DOI: 10.1016/j.csda.2013.07.021
|View full text |Cite
|
Sign up to set email alerts
|

Finding multivariate outliers with FastPCS

Abstract: The Projection Congruent Subset (PCS) is a new method for finding multivariate outliers. Like many other outlier detection procedures, PCS searches for a subset which minimizes a criterion. The difference is that the new criterion was designed to be insensitive to the outliers. PCS is supported by FastPCS, a fast and affine equivariant algorithm which is also detailed. Both an extensive simulation study and a real data application from the field of engineering show that FastPCS performs better than its competi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…Remarkably, the finite sample breakdown point of an estimator can be derived without recourse to concepts of chance or randomness using geometrical features of Email addresses: eric.schmitt@wis.kuleuven.be (Eric Schmitt), viktoria.oellerer@kuleuven.be (ViktoriaÖllerer), kaveh.vakili@wis.kuleuven.be (Kaveh Vakili) a sample alone (Donoho , 1982). Recently, Vakili and Schmitt (2014) introduced the Projection Congruent Subset (PCS) method. PCS computes an outlyingness index, as well as estimates of location and scatter derived from it.…”
Section: Introductionmentioning
confidence: 99%
“…Remarkably, the finite sample breakdown point of an estimator can be derived without recourse to concepts of chance or randomness using geometrical features of Email addresses: eric.schmitt@wis.kuleuven.be (Eric Schmitt), viktoria.oellerer@kuleuven.be (ViktoriaÖllerer), kaveh.vakili@wis.kuleuven.be (Kaveh Vakili) a sample alone (Donoho , 1982). Recently, Vakili and Schmitt (2014) introduced the Projection Congruent Subset (PCS) method. PCS computes an outlyingness index, as well as estimates of location and scatter derived from it.…”
Section: Introductionmentioning
confidence: 99%
“…One way of detecting outliers is to plot the data points (if possible) and visually inspect the resultant plot for points which lie far outside the general distribution. Another way is to run the analysis on the entire dataset, and then eliminating those points which do not meet mathematical 'control limits' for variability from a trend, and then repeating the analysis on the remaining data (Vakili and Schmitt, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…We implemented the MCD using the proportion 0·75, as recommended by Rousseeuw & Driessen (; preliminary analyses revealed that the results were not sensitive to this proportion), with the function CovNAMcd in the r package rrcovNA (Todorov & Filzmoser ). In preliminary analyses, the MCD outperformed a different robust method called the projection congruent subset (Schmitt, Oellerer & Vakili ; Vakili & Schmitt , results not shown).…”
Section: Methodsmentioning
confidence: 99%